Social support and strategies of coping with stress in patients with ulcer disease - Joć, Ewa; Mądro, Agnieszka; Janowski, Konrad; Celiński, Krzysztof; Słomka, Maria (Polish Journal of Public Health, 2012)
Introduction. The etiology of ulcer disease has long been associated with psychogenic factors. After discovering the role of Helicobacter pylori in development of ulcers, the interest in psychosomatic aspects of this disease decreased. However, well controlled studies showed that various facets of psychological stress may still be important factors contributing to this disease, for instance through facilitation of H. pylori infection.Aim. The objective of this study was to explore the role of two stress-related factors – perceived social support and strategies of coping with stress – in patients with ulcerdisease.Material and methods. Sixty-two patients with ulcer disease and one hundred and two healthy controls took part in the study. They were assessed on a measure of coping with stress (Ways of Coping Questionnaire) and social support (Norbeck Social Support Questionnaire).Results. The patients were found to report slightly higher levels of perceived social support than controls. Among coping strategies, patients differed significantly from controls in less frequent use of one coping strategy – cognitive restructuring. Social support was found to be related to certain coping strategies in the patients but not in the control group.Conclusions. Higher levels of reported social support in patients with ulcer disease may be indicative of their greater need for this support due to the disease. Social support and coping strategies are related in patients with ulcer disease and these relationships are bidirectional.